The State of Food Security and Nutrition in the World 2018 - Food; Agriculture Organization of the United Nations (United Nations, 2019)
This year’s report shows that climate variability and extremes – even without conflict – are key drivers behind the recent rise in global hunger and one of the leading causes of severe food crises and their impact on people’s nutrition and health. Climate variability and exposure to more complex, frequent and intense climate extremes are threatening to erode and reverse gains in ending hunger and malnutrition. Furthermore, hunger is significantly worse in countries where agriculture systems are highly sensitive to rainfall, temperature and severe drought, and where the livelihood of a high proportion of the population depends on agriculture.